2019
DOI: 10.1029/2019ms001772
|View full text |Cite
|
Sign up to set email alerts
|

Response of Convective Boundary Layer and Shallow Cumulus to Soil Moisture Heterogeneity: A Large‐Eddy Simulation Study

Abstract: In this study, the impact of varying soil moisture heterogeneity (spatial variance and structure) on the development of the convective boundary layer and shallow cumulus clouds was investigated. Applying soil moisture heterogeneity generated via spatially correlated Gaussian random fields based on a power law model and idealized atmospheric vertical profiles as initial conditions, three sets of large-eddy simulations provide insight in the influence of soil moisture heterogeneity on the ensuing growth of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 57 publications
(97 reference statements)
0
10
0
Order By: Relevance
“…Studies have shown that surface heterogeneities influence the vertical profile of atmospheric states, which is more pronounced under a well‐formed SC condition. (Hadfield et al ., 1992; Patton et al ., 2005; Huang and Margulis, 2009; Han et al ., 2019a). We decompose the wind into three parts based on Equation to study the impact of ambient winds in conjunction with surface heterogeneity on the CBL.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that surface heterogeneities influence the vertical profile of atmospheric states, which is more pronounced under a well‐formed SC condition. (Hadfield et al ., 1992; Patton et al ., 2005; Huang and Margulis, 2009; Han et al ., 2019a). We decompose the wind into three parts based on Equation to study the impact of ambient winds in conjunction with surface heterogeneity on the CBL.…”
Section: Resultsmentioning
confidence: 99%
“…Although the scale range of mesoscale surface heterogeneity is a rough estimation based only on the two time scales τ ∗ and τ e , the findings of multiple studies (e.g., Han et al., 2019; Patton et al., 2005; Taylor et al., 2012, 2011) have supported this scale range for mesoscale surface heterogeneity that significantly influences on the CBL and, further, moist convection. For example, Patton et al.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Han et al. (2019) reported that the horizontal flow generated by soil moisture heterogeneity at the scale of approximately 20 km is the strongest based on their LES results with river‐like soil moisture patterns across a range of approximately 1–100 km.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations